Molecular identification of bacteria isolated from culture medium of the gold-lipped pearl oyster Pinctada maxima larvae - Stenly Wullur; HATOPAN NAPITUPULU; ELVY LIKE GINTING; NOLDY GUSTAF FRANS MAMANGKEY; LETHA LOUISIANAWANTANIA; RADOSLAV SMOLAK; ERICK OGELLO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Wullur S, Napitupulu H, Wantania LL, Ginting EL, Mamangkey NGF, Smolak R, Ogello E. 2020. Molecular identification of bacteria isolated from culture medium of the gold-lipped pearl oyster Pinctada maxima larvae. Biodiversitas 21: 5291-5297.  This study was conducted for the molecular identification of bacteria species isolated from culture medium of the gold-lipped pearl oyster, Pinctada maxima larvae. The pearl oysters were cultured using live-microalgae (Isochrysis sp) and fish waste diet (FWD) as food sources.  Bacteria were isolated from the oyster larvae and identified based on the 16S rRNA gene sequence. The isolated bacteria were grown on agar plates and incubated at 37°C for 24 to 48 hours. Representative colonies of the bacteria were selected and cultured for molecular analysis.  The 16S rRNA genes of the bacteria were amplified and the sequences were matched with the NCBI GenBank database. Seven different colonies were observed based on morphological characters. Similarity test by conducting the Basic Local Alignment Search Tool (BLAST) in the NCBI GenBank database, using the 16S rRNA gene sequences showed that the seven isolates colonies possess high similarity to five bacteria species i.e. Pseudomonas pachastrellae, Vibrio alginolyticus, Bacillus filamentosus, Bacillus cereus and Idiomarina fontislapidosi belonging to four different genera i.e. Bacillus, Staphylococcus, Vibrio, and Alteromonas.